Are workers at risk of occupational injuries due to heat exposure? A comprehensive literature review. (December 2018) - Varghese, Blesson M.; Hansen, Alana; Bi, Peng; Pisaniello, Dino
Highlights: Relationship between heat and work injuries is strong but varies by work location and type of work. Research is needed to characterize specific injuries, workers at risk and injury mechanisms. There is a need for employers and workers to be aware of the health risks during hot weather. Targeted interventions and workplace policies focussed on preventative strategies are needed. Abstract: Rationale: There is increasing concern about occupational illness, injury and productivity losses due to hot weather in a changing climate. Most of the current understanding appears to relate to heat-induced illness, and relatively little regarding injuries. Objectives: This paper sought to summarise the evidence on the relationship between heat exposure and injuries, to describe aetiological mechanisms and to provide policy suggestions and further research directions. Methods: A literature review was conducted using a systematic search for published and grey-literature using Embase, PubMed, Scopus, CINAHL, Science Direct and Web of Science databases as well as relevant websites. Results and conclusions: There was a diversity of studies in terms of occupations, industries and methods utilised. The evidence suggests an imprecise but positive relationship between hot weather and occupational injuries, and the most likely mechanism involves fatigue, reduced psychomotor performance, loss of concentration and reduced alertness. The findings reflect an increased awareness of injury risk during hot weather and the economic benefits associated with averting injury, poor health outcomes and lost productivity. Implications: More work is required to characterise specific injuries and the workers at risk. Policymakers and employers should be aware that heat exposure can lead to occupational injuries with information and training resources developed to aid prevention.